C/EBPα and DEK coordinately regulate myeloid differentiation - Koleva, Rositsa I. (American Society of Hematology, 2012)
The transcription factor C/EBPα is a critical mediator of myeloid differentiation and is often functionally impaired in acute myeloid leukemia. Recent studies have suggested that oncogenic FLT3 activity disrupts wild-type C/EBPα function via phosphorylation on serine 21 (S21). Despite the apparent role of pS21 as a negative regulator of C/EBPα transcription activity, the mechanism by which phosphorylation tips the balance between transcriptionally competent and inhibited forms remains unresolved. In the present study, we used immuno-affinity purification combined with quantitative mass spectrometry to delineate the proteins associated with C/EBPα on chromatin. We identified DEK, a protein with genetic links to leukemia, as a member of the C/EBPα complexes, and demonstrate that this association is disrupted by S21 phosphorylation. We confirmed that DEK is recruited specifically to chromatin with C/EBPα to enhance GCSFR3 promoter activation. In addition, we demonstrated that genetic depletion of DEK reduces the ability of C/EBPα to drive the expression of granulocytic target genes in vitro and disrupts G-CSF–mediated granulocytic differentiation of fresh human BM-derived CD34(+) cells. Our data suggest that C/EBPα and DEK coordinately activate myeloid gene expression and that S21 phosphorylation on wild-type C/EBPα mediates protein interactions that regulate the differentiation capacity of hematopoietic progenitors.